Postispinatus youngi n. gen., n. sp. (Apseudomorpha; Tanaidacea; Crustacea): phylogenetic analysis and taxonomic remarks about kalliapseudids - Santos, Kátia Christol Dos; Santana, William; Pires-Vanin, Ana Maria Setubal (Zootaxa, 2012)
The presence of setae or a sensorial structure on the dactylus of pereopod 1 as one of the defining features of the familyKalliapseudidae is re-evaluated. A new genus, Postispinatus, including the new species P. youngi n. gen., n. sp., isdescribed and thought to belong to the Kalliapseudidae based on phylogenetic analysis. The diagnostic features of newgenus—and species by monotypy —are: basal article of uropod with two curved spiniform processes; exopods on the fourth and fifth pereopods of the manca stage; absence of a maxillule palp.